2014
DOI: 10.25011/cim.v37i1.20864
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CUGBP1 inhibits growth of hepatocellular carcinoma cells

Abstract: Purpose: e multifunctional RNA-binding protein, CUGBP1, regulates splicing, stability and translation of mRNAs. Previous studies have shown that CUGBP1 is expressed at high levels in the liver, although its role in hepatocellular carcinoma is unknown. Our aim was to determine if CUGBP1 could regulate hepatocellular carcinoma growth.Methods: Expression levels of CUGBP1 were analyzed in 70 hepatic carcinoma and 20 normal hepatic tissue samples by immunohistochemistry (IHC). Using lentivirusmediated short hairpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 30 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…In agreement with this prediction, CUGBP1-dependent accumulation of C/EBP␤-HDAC1 complexes leads to the repression of tumor suppressors p53, p21, and C/EBP␣ (15,16). Since previous studies reported the elevation of CUGBP1 in HCC from adult patients (28,29) and showed oncogenic activities of CUGBP1, we expected that liver cancer was inhibited in S302A mice. However, we found that S302A mice have more severe liver cancer under DEN-mediated carcinogenesis.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In agreement with this prediction, CUGBP1-dependent accumulation of C/EBP␤-HDAC1 complexes leads to the repression of tumor suppressors p53, p21, and C/EBP␣ (15,16). Since previous studies reported the elevation of CUGBP1 in HCC from adult patients (28,29) and showed oncogenic activities of CUGBP1, we expected that liver cancer was inhibited in S302A mice. However, we found that S302A mice have more severe liver cancer under DEN-mediated carcinogenesis.…”
Section: Discussionsupporting
confidence: 61%
“…These studies have identified a new function of CUGBP1, which is the regulation of body homeostasis. Several previous reports found that CUGBP1 is elevated in patients with HCC and in mouse liver cancer mediated by DEN (15,28,29). In addition, a recent report showed that CUGBP1 is involved in the development of liver fibrosis, which is one of the critical steps of the development of liver cancer in humans (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Timchenko et al 28. found that CUGBP1 expression was increased in the liver of older individuals and Liu et al 29. recently reported that the suppression of CUGBP1 inhibits the growth of hepatocellular carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although CELF1 is best known for its role in the pathogenesis of Type 1 Myotonic Dystrophy19, it has been previously shown to play a protective role in chemotherapy-induced apoptosis49505152 and was identified as a top driver of colorectal tumourigenesis in an unbiased mutagenesis study53. However, none of these studies have delved into the mechanism by which CELF1 effects these various phenotypes.…”
Section: Discussionmentioning
confidence: 99%